Avaliação das propriedades física e mecânica de cimentos com a incorporação do pó de vidro - Vasconcelos, Arthur de Sousa Lima (Universidade Federal de São Carlos, 2022)
The use of glass powder in the cement composition as supplementary cementitious material (SCM) is an excellent alternative to mitigate the amount of waste generated by the glass industry itself, as well as reduce the amount used of clinker, the main raw material of Portland cement (PC). Moreover, the incorporation of glass can bring benefits in the properties of cementitious matrices both in the fresh and hardened states. To analyze the physical and mechanical properties of the incorporation of glass powder in the cement composition and meet the requirements of NBR 16697, the setting times, normal consistency of the paste and compressive strength of Portland cement matrices with incorporation of glass powder at 0%, 5%, 15% and 25% were determined. In the compressive strength test, 50x100mm cylindrical specimens were broken at ages of 3, 7 and 28 days for each cement. The materials used in this study are: CP V-ARI, normal sand and the glass powder from amber colored bottles with particle size passing the #200 mesh sieve. The increase in the incorporation of ground glass in the analyzed cements provided a higher fineness modulus and initial setting time directly impacting the workability and decrease in the initial mechanical strength due to the pozzolanicity of the glass. At 28 days, a reduction of 8.83%, 19.45%, and 26.72% was observed for cements with contents of 5%, 15% and 25% of glass powder, respectively, in relation to the reference with compressive strength of 54.12 MPa. Furthermore, the statistical analysis of the mechanical strength indicated that there is no statistical difference between the ages analyzed for the reference mixture and with 5% glass powder. Among the tests performed, the minimum requirements were met for all cements studied except for the compressive strength at 7 days of age for CP75PV25, which obtained the value of 32.13 MPa. Thus, the mix that relates the highest incorporation of glass powder in the composition of the cement and meets the minimum requirements established by NBR 16697 for the tests developed, is the cement with the incorporation of 15% ground glass as mineral addition.
Evaluation of the physical and mechanical properties of cements with the incorporation of glass powder
Keywords: Cimento; Pó de vidro; Material cimentício suplementar; Comportamento mecânico; Cement; Glass powder; Supplementary cementitious material; Mechanical behavior; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL